1999
DOI: 10.1016/s0378-1097(99)00279-7
|View full text |Cite
|
Sign up to set email alerts
|

Binding of extracellular matrix laminin to Escherichia coli expressing the Salmonella outer membrane proteins Rck and PagC

Abstract: Salmonella Rck and PagC are closely related virulence-associated proteins. When expressed in non-adherent, non-invasive laboratory Escherichia coli, both proteins localised to the outer membrane. Only Rck conferred adhesion to culture cells, but both proteins induced bacterial binding to the cell monolayer background, to extracellular matrix (ECM) preparations, and to the ECM component laminin. Laminin binding was saturable and competitive, and was reduced by removal of carbohydrate side chains. Pre-incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…However, as the molecular mechanisms of these proteins become characterized, it is apparent that conserved functions can be assigned to several members of this family. Rck, PagC (Salmonella choleraesuis), and Ail were shown to mediate serum resistance (3-5, 23, 24), whereas adhesion and/or invasion properties have been observed in all of the aforementioned proteins, with the exception of Y. pseudotuberculosis Ail (25)(26)(27)(28)(29). Furthermore, functional fH and C4BP binding have now been described in Rck (21,30) and Y. enterocolitica and Y. pseudotuberculosis Ail (10,11,15).…”
Section: Discussionmentioning
confidence: 99%
“…However, as the molecular mechanisms of these proteins become characterized, it is apparent that conserved functions can be assigned to several members of this family. Rck, PagC (Salmonella choleraesuis), and Ail were shown to mediate serum resistance (3-5, 23, 24), whereas adhesion and/or invasion properties have been observed in all of the aforementioned proteins, with the exception of Y. pseudotuberculosis Ail (25)(26)(27)(28)(29). Furthermore, functional fH and C4BP binding have now been described in Rck (21,30) and Y. enterocolitica and Y. pseudotuberculosis Ail (10,11,15).…”
Section: Discussionmentioning
confidence: 99%
“…The Salmonella protein Rck was first identified as a virulence factor required for serum resistance and host cell invasion (9). It was later found that both Rck and a similar protein, PagC, are able to bind laminin, and their expression in Escherichia coli confers the capacity for adherence to basement membranes and host cells (11). Adherence to ECM is also believed to contribute to virulence of Bacteroides fragilis, Borrelia burgdorferi, Haemophilus influenzae, and Moraxella catarrhalis (6,18,19,53).…”
mentioning
confidence: 99%
“…Heffernan and coworkers (10) have demonstrated that Rck appears to affect the formation and interaction of the MAC on the bacterial surface, as Rck-expressing cells are more sensitive to trypsin release of C9 and display fewer SDS-resistant C5b-9 complexes, suggesting disruption of MAC function (8). In addition to serum resistance, Rck expression in E. coli mediates adherence and invasion to cultured eukaryotic cell lines (10) as well as binding to laminin and fibronectin (11).…”
mentioning
confidence: 99%